1989
DOI: 10.1109/16.34236
|View full text |Cite
|
Sign up to set email alerts
|

Interface state generation under long-term positive-bias temperature stress for a p/sup +/ poly gate MOS structure

Abstract: Abstraet-Long-term reliability for a p+ poly gate MOS structure was tested under low electric field bias temperature (BT) stress in comparison with an n+ poly gate. A significant increase in interface state density was observed for the pf poly gate MOS structure under positive bias conditions. This phenomenon was not observed in the n + poly gate case. The mechanism for this interface state increase was investigated in detail. Several possible causes, such as mobile ions, excess boron concentration in the gate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…10 It has been reported that the trapped holes can also induce slow states 11 and the hole injection can enhance the positive bias temperature instability for metal-oxide-semiconductor field effect transistors ͑MOSFETs͒ with pϩ poly-Si gate. 9 After hole injection is terminated, the generation of interface states can continue. 1,13 This post-stress degradation reduces device lifetime 1 and its physical mechanism is still not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 It has been reported that the trapped holes can also induce slow states 11 and the hole injection can enhance the positive bias temperature instability for metal-oxide-semiconductor field effect transistors ͑MOSFETs͒ with pϩ poly-Si gate. 9 After hole injection is terminated, the generation of interface states can continue. 1,13 This post-stress degradation reduces device lifetime 1 and its physical mechanism is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…However, instabilities can be induced both in the bulk of SiO 2 and at the SiO 2 /Si interface under a number of stress conditions, such as hot carrier injection, [1][2][3] Fowler-Nordheim injection, 4 irradiation, [5][6][7] and bias temperature stress. 8,9 Damages can be caused by both electrons and holes. This article focuses on the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Neugebauer et al 14 reported current decay for both positive and negative gate biases. Hiruta et al, 15 Ushizaka and Sato 16 and Abadeer et al 17 showed that the interface-state density at the Si-SiO 2 interface increases when the gate is biased positively. These instabilities are summarized in Table III.…”
Section: Comparison With Instabilities Reported Elsewherementioning
confidence: 98%
“…Neugebauer et al 14 reported current decay for both positive and negative gate bias. Hiruta et al 15 found that the interface-state density at the Si-SiO 2 interface increases when the gate is biased positively. Ushizaka and Sato 16 and Abadeer et al 17 discussed the interface-state density increase in detail.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation